Family Members’ Psychosocial Support in Palliative Inpatient Care: A Cross-Sectional Study - Soikkeli-Jalonen, Anu; Mishina, Kaisa; Saarinen-Nassar, Johanna; Kesonen, Pauliina; Virtanen, Heli; Karukivi, Max; Haavisto, Elina (SAGE Publications, 2026)
To evaluate the family members’ psychosocial support during specialist palliative inpatient care. Cross-sectional study. The “Family Involvement Scale–Psychosocial Support in Palliative Inpatient Care” (FIS-PS-InPal) questionnaire was used to collect data from family members from specialized palliative care wards across Finland. Data were analyzed using descriptive statistics. In total, 171 family members from 16 wards across Finland participated in the study. Family members evaluated the support they received as close to ideal, with 19.9% of participants reporting that the support was less than desired. They rated psycho-emotional support and support practices as the strongest and informational support as the weakest. The psychosocial support that family members receive in specialist palliative care is generally adequate. However, efforts should be made to improve how information is communicated. The study underscores the importance of evaluating and addressing the unique support implementation for families in palliative care.